IPO Patterns in Euronext After the Global Financial Crisis of 2007‑ 2008 - Silva, Nuno (2021)
This paper looks into the pricing patterns of 161 IPOs that occurred in 2009‑ 2017 in the Euronext markets of Amsterdam, Brussels, Lisbon and Paris. Across all the IPOs, we find a first‑ day raw return of 1.4% and an industry adjusted return of 1.2%. After one year, the average raw returns are slightly higher (around 4.5%) and the average adjusted returns are negative (around ‑ 2.7%). These first day returns are lower whilst the long run returns are higher than those reported in other studies, most notably in those that use periods that overlap our sample. Healthcare is the industry that presents higher initial underpricing (2.3% industry‑ adjusted return), whilst the Technology industry presents the highest one year underperformance (‑ 29.5% industry adjusted return). Our findings are in line with the market conditions and investor sentiment hypotheses according to which, when market conditions are poor (crises), uninformed investors are not so active and optimistic in the IPO market, hence underpricing and subsequent underperformance tend to be lower. A possible explanation for the different outcomes is that the global financial crises dampened persistently the activity and optimism of uninformed IPO investors, even when the European stock market and the economy in general were already recovering.